# Come consideri il fattore 1 - 2.25x ^ 8 ?

#### Risposta:

1-2.25x^8

=1/4(root(4)(2)-root(4)(3)x)(root(4)(2)+root(4)(3)x)(sqrt(2)+sqrt(3)x^2)(sqrt(2)-root(4)(24)x+sqrt(3)x^2)(sqrt(2)+root(4)(24)x+sqrt(3)x^2)

#### Spiegazione:

Alcune identità che useremo:

a^2-b^2 = (a-b)(a+b)

Somma dell'identità del quarto potere:

a^4+b^4 = (a^2-sqrt(2)ab+b^2)(a^2+sqrt(2)ab+b^2)

Così:

1-2.25x^8

=1/4(4-9x^8)

=1/4(2^2-(3x^4)^2)

=1/4(2-3x^4)(2+3x^4)

=1/4((sqrt(2))^2-(sqrt(3)x^2)^2)(2+3x^4)

=1/4(sqrt(2)-sqrt(3)x^2)(sqrt(2)+sqrt(3)x^2)(2+3x^4)

=1/4((root(4)(2))^2-(root(4)(3)x)^2)(sqrt(2)+sqrt(3)x^2)(2+3x^4)

=1/4(root(4)(2)-root(4)(3)x)(root(4)(2)+root(4)(3)x)(sqrt(2)+sqrt(3)x^2)(2+3x^4)

=1/4(root(4)(2)-root(4)(3)x)(root(4)(2)+root(4)(3)x)(sqrt(2)+sqrt(3)x^2)((root(4)(2))^4+(root(4)(3)x)^4)

=1/4(root(4)(2)-root(4)(3)x)(root(4)(2)+root(4)(3)x)(sqrt(2)+sqrt(3)x^2)(sqrt(2)-sqrt(2)root(4)(2)root(4)(3)x+sqrt(3)x^2)(sqrt(2)+sqrt(2)root(4)(2)root(4)(3)x+sqrt(3)x^2)

=1/4(root(4)(2)-root(4)(3)x)(root(4)(2)+root(4)(3)x)(sqrt(2)+sqrt(3)x^2)(sqrt(2)-root(4)(24)x+sqrt(3)x^2)(sqrt(2)+root(4)(24)x+sqrt(3)x^2)#